Investigating the effect of insurance literacy on sustainable performance in small and medium enterprises / Murtala Garba, Fauzilah Salleh and Usman Ahmed Hafiz - Garba, Murtala; Salleh, Fauzilah; Ahmed Hafiz, Usman (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
The importance of sustainability in organisations is growing due to consumer demand, which has elevated sustainability from a nice-to-have to an essential business concern. The study explored the impact of insurance literacy on the sustainable performance of Nigerian Small and Medium Enterprises (SMEs). The study examined the influence of insurance knowledge, understanding insurance and perceived benefit of insurance on economic and social sustainability of Nigeria’s SMEs. The study employed the structural equation method (SEM-AMOS) to analyse data from 364 SME managers in Nigeria. Results from the analysis showed that understanding insurance and perceived benefits significantly affect economic and social sustainability. Insurance knowledge had a positive but insignificant effect on social sustainability. The findings can help SMEs shape sustainable performance strategies. The study recommends promoting mass enlightenment campaigns to improve SMEs’ insurance literacy. SMEs should focus on improving insurance literacy, with insurers educating them about its importance. Policymakers should prioritize insurance literacy and develop programs to increase it.